The Pogil Learning Model and Students' Critical Thinking Improvement in History Subject - Nurul Umamah; Herlinatus Sholehah (Pancaran Pendidikan, 2022)
Critical thinking skills (CTS) are important skills for students to filter information in the era of globalization. With the rapid growth of education, there goes the more significant challenges and advanced-technological transformation. GEN Z learners, called "digital natives," quickly obtained the information. The ability to think critically is crucial to help the students' filter information accurately. However, several kinds of research reported that students with low CTS. Previous research claimed theoretically that POGIL learning model research was effective for improving the CTS. This research was to verify the effectiveness of POGIL in history learning. In this quasi-experimental design, as many as 30 students testified their CTS performance on their pre-and post-learning papers. The data were analyzed by using t-test. The result shows that there is a significant difference (p< 0.005) between after treatment using POGIl and before. The average CTS scores of students before being taught by POGIL was 46.8, and after learning was 81.7. It shows that the POGIL learning model effectively improved the students' CTS.